2015
DOI: 10.1089/elj.2013.0238
|View full text |Cite
|
Sign up to set email alerts
|

Informing Electorates via Election Law: An Experimental Study of Partisan Endorsements and Nonpartisan Voter Guides in Local Elections

Abstract: Many legal scholars and political practitioners advocate using election law to increase voters' access to political information, either by providing such information directly on ballots or in ballot pamphlets. To date, however, little empirical evidence exists to guide policymakers and judges charged with weighing the benefits of such legal interventions against any costs they might impose. We address this gap by conducting survey experiments to examine three types of political information that legal intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Scholars in recent years have developed methods for creating comparable measures of candidate and voter ideology (Boudreau, Elmendorf, and MacKenzie , ; Jessee ; Joesten and Stone ; Shor and Rogowski ) . One method combines candidates’ known policy views with surveys that ask voters whether they support those policies.…”
Section: Spatial and Racial Votingmentioning
confidence: 99%
“…Scholars in recent years have developed methods for creating comparable measures of candidate and voter ideology (Boudreau, Elmendorf, and MacKenzie , ; Jessee ; Joesten and Stone ; Shor and Rogowski ) . One method combines candidates’ known policy views with surveys that ask voters whether they support those policies.…”
Section: Spatial and Racial Votingmentioning
confidence: 99%
“…The findings from this paper also add nuance to the cross-racial mobilization literature, which largely uses observational analyses to assess the successes and failures of candidates in high-profile elections. The present paper, which relies on experimental analyses and a lowsalience election, shows that cues may operate differently in elections of varying degrees of salience (Bernhard and Freeder, 2018;Boudreau, Elmendorf, and MacKenzie, 2015a;2015b).…”
Section: Discussionmentioning
confidence: 87%
“…For example, Arceneaux and Kolodny (2009) showed that politically uninformed Republicans can use a liberal interest group’s endorsement to help them choose candidates who share their partisanship. Similarly, Boudreau, Elmendorf, and MacKenzie (2015) demonstrated that endorsements from political parties and well-known politicians with ideological reputations help uninformed citizens to make decisions that are comparable to those who are informed. An open question for future research is whether and when other types of endorsements—particularly those from politically active groups whose ideological reputations are less clear (e.g., law enforcement organizations)—provide citizens with substitutes for the political information that they lack.…”
Section: Contributions To Research On Political Endorsementsmentioning
confidence: 99%